66.7k views
3 votes
Find the inverse of the given function.

Find the inverse of the given function.-example-1

2 Answers

5 votes

Answer:


f(x)^(-1)= 4x^(2) -3 .

Explanation:

Given :
f(x) =-(1)/(2)√(x+3).

To find : Find the inverse of the given function.

Solution : We have given


f(x) =-(1)/(2)√(x+3).

Step 1: take f(x) = y


y =-(1)/(2)√(x+3).

Step 2 : Inter change y and x.


x =-(1)/(2)√(y+3).

Step 3 : Solve for y

Taking square both sides


x^(2) = (1)/(4)(y+3).

On multiply both sides by 4.


4x^(2) = (y+3).

On subtraction both sides by 3.


4x^(2) -3 = y.

Here,
f(x)^(-1)= y is inverse of f(x)


f(x)^(-1)= 4x^(2) -3 .

Therefore,
f(x)^(-1)= 4x^(2) -3 .

User Trying Tobemyself
by
6.0k points
3 votes

For this case we must find the inverse of the following function:


f (x) = - \frac {1} {2} \sqrt {x + 3}

We follow the steps below:

Replace f(x) with y:


y = -\frac {1} {2} \sqrt {x + 3}

We exchange the variables:


x = - \frac {1} {2} \sqrt {y + 3}

We solve for "y":


- \frac {1} {2} \sqrt {y + 3} = x

Multiply by -2 on both sides of the equation:


\sqrt {y + 3} = - 2x

We raise both sides of the equation to the square to eliminate the radical:


(\sqrt {y + 3}) ^ 2 = (- 2x) ^ 2\\y + 3 = 4x ^ 2

We subtract 3 from both sides of the equation:


y = 4x ^ 2-3

We change y by f ^ {- 1} (x):


f ^ {- 1} (x) = 4x ^ 2-3

Answer:
f ^ {- 1} (x) = 4x ^ 2-3

User Nikola Gedelovski
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.